TERNATE SOCIETY DEVELOPMENT DILEMMA IN FACING ATTRACTIONS BETWEEN TRADITION AND MODERNITY - Muhammad, Syahril (Historia: Jurnal Pendidik dan Peneliti Sejarah, 2011)
The purpose of this research is to find information about the Ternatenese and Ternate aristocracy in facing the attraction between tradition and modernity as an effort to formulate a conceptual frame of the local society. Interview and documentary is used to gather data. Several informants that were chosen purposively were interviewed in this research. Documentary study was done of the primary and secondary sources. The result of this research is (1) Ternate aristocracy has a responsive reaction toward modernization. This means, they are not only accepting new values, but also conserving traditional values that is relevance to the society life development and; (2) Tradition and modernization attractions in Ternate aristocracy, in the political access, is improving. Some aristocrats are often used by the local politicians for their political purpose.